Peningkatan Hasil Pembelajaran Tematik Terpadu Menggunakan Model Numbered Heads Together di Kelas V SD - Gusti Suryani; Muhammadi Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This research purposed to describe the improvement thematic learnig outcomes using  the model Numbered Heads Together (NHT) Grade V in Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 20 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection .The result of planning observation in cycle I is 81,94% (B) and it increase to be 94,44% (A)  in cycle II. The result of teacher aspect observation in cycle I is 79,68% (C)  and it increase to be 93,75% (A) in cycle II. The result of student aspect observation in cycle I is 79,68% (C)  and it increase to be 90,62% (A) in cycle II. The learning outcomes in cycle I is 71,5 (C) and it increase to be 82 (B) in cycle II. The research showed the scientific approach can improve the integrated thematic learnig outcomes Grade II at Elementary School.